Emotional labor in nursing praxis - José Manuel da Silva Vilelas; Paula Manuela Jorge Diogo
Healthcare work is, by nature, an activity full of intense emotions and therefore, is opportune ground for exploring emotions in the workplace in different contexts of nursing care. It is a very fertile terrain if care is focused on the emotions of the client, nurses, healthcare teams, and on the interaction of all actors involved. This article presents a theoretical reflection exploring the concept of emotional labor in the context of nursing care. Theoretical references from several fields of knowledge, namely sociology and nursing, have been adopted to conceptualize the theme. Studies on emotional labor have contributed toward the understanding of the key issue of emotional management in healthcare institutions and both its positive and negative impact on clients and professionals. The development of the theme of emotional labor in nursing has given rise to numerous theoretical approaches and perspectives explaining this concept.